Ultrasound Guided Platelets Rich Plasma Injection as Pain Management Method for Knee Pain in Partial Medial Collateral Ligament Injury - Algawwam, Hayder Ghali; KhairuAllah, Huda Ihsan; Mohammad, Abdullah Ahmed; Ali, Nuha Abdulwahab Muhammed (Journal of medical and pharmaceutical sciences, 2021)
Objective: the aim of this study is to evaluate effectiveness of ultrasound guided platelets rich plasma (PRP) injection as pain management method in patients complaining from partial injury of medial collateral ligament Patients and Methods: a retrospective study conducted for the period from January 1, 2017 until July 31, 2019, 31 patients (21 females and 10 males) visited Dr Abdullah Ahmed Mohammad private clinic in Kirkuk, Iraq because of knee pain as a result of partial tear of medial collateral ligament, they received ultrasound guided PRP injections. The PRP was obtained by centrifugation of patient’s own blood. The degree of response to treatment grading was as following: excellent, good, fair and poor. Results: the mean age was 52 ± 1.5 years, Two-thirds of patients were female and one-third were male, (n: 27, 87.0%) of patients received one sessions, excellent or good response to treatment found in most of patients (n: 28,90.3 %) while only three patients (9.7%) didn’t respond to treatment, there was a significant statistical difference between the 2 groups (p˂0.01) Conclusion: ultrasound guided PRP injection appears effective and improved clinical outcome in knee pain in MCL partial tear